Past the Precipice? Projected Coral Habitability Under Global Heating. Issue 5 (5th May 2022) - Kalmus, P.; Ekanayaka, A.; Kang, E.; Baird, M.; Gierach, M.
Abstract: Coral reefs are rapidly declining due to local environmental degradation and global climate change. In particular, corals are vulnerable to ocean heating. Anomalously hot sea surface temperatures (SSTs) create conditions for severe bleaching or direct thermal death. We use SST observations and CMIP6 model SST to project thermal conditions at reef locations at a resolution of 1 km, a 16‐fold improvement over prior studies, under four climate emissions scenarios. We use a novel statistical downscaling method which is significantly more skillful than the standard method, especially at near‐coastal pixels where many reefs are found. For each location we present projections of thermal departure (TD, the date after which a location with steadily increasing heat exceeds a given thermal metric) for severe bleaching recurs every 5 years (TD5Y) and every 10 years (TD10Y), accounting for a range of post‐bleaching reef recovery/degradation. As of 2021, we find that over 91% and 79% of 1 km 2 reefs have exceeded TD10Y and TD5Y, respectively, suggesting that widespread long‐term coral degradation is no longer avoidable. We project 99% of 1 km 2 reefs to exceed TD5Y by 2034, 2036, and 2040 under SSP5‐8.5, SSP3‐7.0, and SSP2‐4.5 respectively. We project that 2%–5% of reef locations remain below TD5Y at 1.5°C of mean global heating, but 0% remain at 2.0°C. These results demonstrate the importance of further improving ecological projection capacity for climate‐vulnerable marine and terrestrial species and ecosystems, including identifying refugia and guiding conservation efforts. Ultimately, saving coral reefs will require rapidly reducing and eliminating greenhouse gas emissions. Plain Language Summary: Coral reefs face many challenges, but the most serious is climate change. Hotter oceans can kill corals via expulsion of their food‐producing algae and eventual starvation, or by cooking them to death. We used satellite data and the latest global Earth system models to project when the world's coral reefs are expected to surpass a severe bleaching temperature threshold at 1‐km‐square locations. To account for post‐bleaching coral recovery times, we project the year after which each location will experience bleaching conditions at least once per 5 and 10 years. As of 2021, we estimate that over 91% and 79% of reef locations will experience bleaching conditions at least once per 10 and 5 years, respectively, suggesting that widespread long‐term coral degradation is no longer avoidable. We estimate that 99% of reefs will experience bleaching conditions every 5 years by 2040, 2036, and 2034 under progressively higher future emissions scenarios (SSP2‐4.5, SSP3‐7.0, and SSP5‐8.5). These results demonstrate the importance of improving ecological projection capacity for climate‐vulnerable marine and terrestrial species and ecosystems, including identifying refuge locations and guiding conservation efforts, and rapidly reducing greenhouse gas (GHG) emissions. Key Points: We project over 91 percent of coral reefs will now experience severe‐bleaching‐level ocean heat recurring at least once every 10 years We project over 99 percent of reefs will experience severe‐bleaching‐level ocean heat at least twice per 10 years by 2036 under SSP3‐7.0 We find SSP1‐2.6 to be the only scenario not consistent with near‐complete global severe degradation or loss of coral reefs